Using financial instruments and PPP schemes for building resilience to natural disasters - Villalba-Romero, Felix; Liyanage, Champika (Elsevier, 2021)
Traditionally, consequences and damages occur from natural disasters/hazards have been managed after the event takes place and political leaders have obtained consensus to set priority for the use of resources to deal with the disasters. This also includes engaging people and institutions through a plethora of collaborative forms. Currently, due to climate change issues, natural disasters are mostly recurrent and, therefore, require preparation of the society to have a greater capacity of resistance to minimize the damages caused by the disasters through Disaster Risk Reduction (DRR) and Disaster Risk Management (DRM) tools. The economic impact of the climate change induced disasters/hazards has led to the introduction of Disaster Risk Financing (DRF) to cover the direct and indirect economic losses incurred by the society. DRF is under the umbrella of DRM and it covers the financial management of DRM actions with the use of necessary Financial Instruments (FI). The terms DRM, DRR, DRF and FI are very much interlinked and, thus needs careful consideration of what each term means and what each of their roles are in the broader disaster management concept. The purpose of this research is to partly fulfill this purpose by identifying the role of DRF and FI with the use of a systematic review process.
La editorial no autorizó el acceso abierto al capítulo de libro. Se solicita mantenga el acceso cerrado. El copyright pertenece en exclusiva al editor.
Keywords: Financial instruments; PPP schemes; Building resilience; Disasters